Hubungan Pengetahuan Lingkungan Dan Status Sosial Ekonomi terhadap Perilaku Hidup Bersih dan Sehat Masyarakat di Desa Nelayan Bontosunggu Kabupaten Kepulauan Selayar - Nur Syamsinah; Yusminah Hala; Muhiddin Palennari (UNM Journal of Biological Education, 2022)
Good behavior in maintaining health can improve a person's quality of life for the better and more prosperous. One of them is by implementing clean and healthy living behavior. Clean and healthy living behavior (PHBS) can be influenced by several factors, including environmental knowledge factors and socioeconomic status factors. Knowing the relationship between environmental knowledge and socio-economic status on the clean and healthy behavior of the community in Bontosunggu Fisherman Village, Selayar Islands Regency. Research design Correlation descriptive method with cross sectional approach. random sampling technique, a total sample of 125 respondents is the Head of the Family of the Fisherman Village of Bontosunggu. based on the results of the Pearson correlation for environmental knowledge and socioeconomic status is 0.486. This implies that environmental knowledge and socioeconomic status have a significant relationship with the achievement of clean and healthy living behavior in the moderate category and form a positive relationship. The results of the study found that there was a relationship between environmental knowledge and socioeconomic status with Clean and Healthy Behavior of the Bontosunggu Fisherman Village community. It is hoped that the community will be more active in seeking health information related to Clean and Healthy Living Behavior so that they have good knowledge about Clean and Healthy Life Behavior and will be motivated to do or apply it in their family.